“Explicitly implicit”: examining the importance of physician nonverbal involvement during error disclosures1 (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY/PRINCIPLES: Medical errors are prevalent, but physicians commonly lack the training and skills to disclose them to their patients. Existing research has yielded a set of verbal messages physicians should communicate during error disclosures. However, considering the emotional message contents, patients likely derive much of the meaning from physicians’ nonverbal behaviours. The purpose of this study was to test the causal effects of physicians’ nonverbal communication on error disclosure outcomes. METHODS: At a university hospital in the Southeastern United States, 318 patients were randomly assigned to three treatment groups. The first group watched a video vignette of a verbally and nonverbally competent error disclosure by a person acting as a physician. The second group was exposed to a verbally competent but nonverbally incompetent error disclosure. The third group read an error disclosure transcript. Then, all patients responded to measures of closeness, trust, forgiveness, satisfaction, distress, empathy, and avoidance. RESULTS: The results evidenced that holding the verbal message content constant, physician nonverbal involvement was significantly associated with higher patient ratings of closeness, trust, empathy, satisfaction, and forgiveness, and with lower ratings of patient emotional distress and avoidance. These associations were not affected by patient predispositions such as sex, ethnicity, religion and previous experiences with medical errors. CONCLUSION: The findings of this study imply that nonverbal communication has a significant impact on error disclosure outcomes and thus should be considered as an important component of future research and disclosure training efforts.